Content validity of a patriotism questionnaire for Rodha Basa media-based learning using Aiken’s V index - Aginia Ashari; Sri Yamtinah; Endrise Septina Rawanoko (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2026)
Patriotism is one of the essential character values that should be instilled in elementary school students through contextual and meaningful learning. Although previous studies have widely discussed character education and patriotism, limited attention has been given to the availability of validated measurement instruments integrated with local culture-based learning media, particularly Rodha Basa media. This study aimed to analyze the content validity of a patriotism questionnaire designed for elementary school students within the context of Rodha Basa media-based learning using Aiken’s V index. A quantitative descriptive method was employed, with data collected through expert judgment involving six validators consisting of two academics and four elementary school practitioners using a validation sheet. Content validity was analyzed using Aiken’s V based on a four-point relevance scale. The results showed that both the pre-test and post-test questionnaires each contained 15 valid items, with Aiken’s V index values ≥ 0.78. The questionnaire demonstrated good content validity, ranging from moderate to high categories, and was considered appropriate for research use. These findings indicate that the developed instrument shows potential for measuring patriotism among elementary school students in a valid and reliable manner within the context of Rodha Basa media-based learning.